Postnatal Development of the Testis in the Rat: Morphologic Study and Correlation of Morphology to Neuroendocrine Parameters. (April 2015) - Picut, Catherine A.; Remick, Amera K.; de Rijk, Eveline P.C.T.; Simons, Michelle L.; Stump, Donald G.; Parker, George A.
Histopathologic examination of the testis from juvenile rats is often necessary to characterize the safety of new drugs for pediatric use and is a required end point in male pubertal development and thyroid function assays. To aid in evaluation and interpretation of the immature testis, the characteristic histologic features of the developing rat testis throughout postnatal development are described and correlated with published neuroendocrine parameter changes. During the neonatal period (postnatal day [PND] 3–7), seminiferous tubules contained gonocytes and mitotically active immature Sertoli cells. Profound proliferation of spermatogonia and continued Sertoli cell proliferation occurred in the early infantile period (PND 8–14). The spermatogonia reached maximum density forming double-layered rosettes with Sertoli cells in the late infantile period (PND 15–20). Leptotene/zygotene spermatocytes appeared centrally as tubular lumina developed, and individual tubules segregated into stages. The juvenile period (PND 21–32) featured a dramatic increase in number and size of pachytene spermatocytes with the formation of round spermatids and loss of "infantile" rosette architecture. In the peri-pubertal period (PND 32–55), stage VII tubules containing step 19 spermatids were visible by PND 46. The presented baseline morphologic and endocrinologic information will help pathologists distinguish delayed development from xenobiotic effects, determine pathogenesis when confronted with nonspecific findings, and identify sensitive time points for targeted study design.